Legal Responsibility of Marketplaces in Distributing iQIYI Digital Services and Consumer Protection in Indonesia - Suci, Indah Meisyana; Nugroho, Andriyanto Adhi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
This study concludes that the distribution of unauthorized iQIYI digital services through marketplaces creates inherent legal defects, as access remains revocable by the authorized provider, exposing consumers to the risk of unilateral account blocking and potential systematic losses. Accordingly, marketplaces should not be treated as passive intermediaries; their platform control and economic benefits justify the application of Absolute Responsibility for consumer losses arising from such transactions. This research employs a normative legal method, combining statutory and conceptual approaches, with a focus on Indonesian consumer protection law and electronic commerce regulation. The analysis demonstrates that intermediary-based liability models are inadequate to address risks inherent in non-physical and revocable digital services. To operationalize this accountability, marketplaces must ensure accurate risk disclosure, verify seller legitimacy, handle complaints effectively, and implement measurable loss-recovery mechanisms. Finally, regulatory alignment of the Government Regulation on Trade Through Electronic Systems with consumer protection principles, including enforceable algorithmic accountability, remains necessary to strengthen supervision and legal certainty in Indonesia's digital commerce ecosystem.